Óbitos infantis e fetais na região de Piracicaba, 2010 a 2013 - Guiro Pacheco, Cecília; Sarmento de Souza Aranda, Clelia Maria; Cruz Perecin, Glaucia Elisa; Diniz Ferreira de Godoy, Luciana Cristina (BEPA. Boletim Epidemiológico Paulista, 2014)